Women self-help farmers’ cooperative society and community development in Central Cross River State, Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study was carried out to investigate Women Self-help Farmers’ Cooperative Society and Community Development in Central Cross River State, Nigeria. To give direction to the study, one hypothesis was formulated from the objective of the study in addition to the research question. Relevant literature and theory were reviewed. The exploratory survey design was adopted for the study, and Taro Yamane formula was used to draw 480 respondents. The study adopted multiple sampling procedures (i.e. the purposive, stratified random sampling, and systematic). Method of data collection used was questionnaire and in-dept-interview. Pearson Product Moment Correlation Coefficient was used to analyze the data. Findings from the study indicates significant relationship between women self-help Farmers’ Cooperative Society and community development. In particular, women involvement in farmers’ cooperative societies, revealed significant relationship with community development with indicators that include: creation of employment, healthy living, among others. Base on the findings, the following recommendations were made among others: There is need for appropriate legislation at the State and Local government levels to encourage self-help cooperative society at the rural area; financial credit pool should be created at the local government Areas to be accessed through women Associations.
Keywords: Women self-help; farmers; cooperative society; employment; healthy living; and community development